Orgasmolepsy in Narcolepsy Type 1 Responsive to Pitolisant: A Case Report - Pellitteri G (Dove Medical Press, 2020)
Gaia Pellitteri,1,2 Pierluigi Dolso,1 Mariarosaria Valente,1,2 Gian Luigi Gigli1– 3 1Clinical Neurology Unit, Department of Neurosciences, Udine University Hospital, Udine, Italy; 2Department of Medicine (DAME), University of Udine, Udine, Italy; 3Department of Mathematics, Informatics and Physics (DMIF), University of Udine, Udine, ItalyCorrespondence: Gaia PellitteriClinical Neurology Unit, Department of Neurosciences, Udine University Hospital, P.le S. Maria Della Misericordia 15, Udine 33100, ItalyTel +39 3343351338Fax +39 0432 552287Email pellitteri.gaia@gmail.comAbstract: We describe a case of a young male patient with narcolepsy type 1 (NT1), who developed generalized cataplexy attacks during sexual intercourses, on which we have obtained a satisfactory control with pitolisant. Orgasmolepsy is an uncommon feature of NT1 that has been poorly described in the literature. The prevalence of this condition is unclear, as it is reasonably underreported by patients for embarrassment and not well investigated by physicians. Pitolisant is a novel treatment for narcolepsy, effective on excessive daytime sleepiness and cataplexy by modulating the histaminergic system. Real-world data collection on pitolisant efficacy and safety is still ongoing. However, pitolisant effectiveness on orgasmolepsy in NT1 has no precedent in the literature. Orgasmolepsy and other sexual disturbances should be actively searched in narcoleptic patients and, if present, may guide clinicians to prefer pitolisant or sodium oxybate, avoiding antidepressants for their possible sexual side effects.Keywords: NT1, cataplexy, sexual dysfunction, narcolepsy treatment